Dispersal limitation determines the ecological processes that regulate the seasonal assembly of bacterial communities in a subtropical river - Zhu, Aiping; Liang, Zuobing; Gao, Lei; Xie, Zhenglan (Frontiers in Microbiology, 2024)
Bacteria play a critical crucial role in pollutant degradation, biogeochemical cycling, and energy flow within river ecosystems. However, the underlying mechanisms governing bacterial community assembly and their feedback response to environmental factors at seasonal scales in subtropical rivers remain elusivepoorly understood. In this study, we conducted 16S rRNA gene amplicon sequencing on water samples from the Liuxi River to investigate the composition, assembly processes, and co-occurrence relationships of bacterial communities during both the wet season (WS) and dry season (DS). The results demonstrated that seasonal differences in hydrochemistry significantly influenced the composition of bacterial communities. with aA more heterogeneous community structure and increased alpha diversity were observed during the DSdry season along with increased alpha and functional diversity. Water temperature emerged as the primary driver for seasonal changes in bacterial communities. Dispersal limitation predominantly governed community assembly, however, during the dry season, its contribution increased during DS due to decreased immigration rates. Co-occurrence network analysis revealed reveals that mutualism played a prevailing role in shaping bacterial community structure. Compared to the wet seasonWS, the network of bacterial communities exhibited higher modularity, competition, and keystone species during the dry seasonDS, resulting in a more stable community structure. Although keystone species displayed distinct seasonal variations, Proteobacteria and Actinobacteria were consistently abundant keystone species maintaining network structure in both seasons. Our findings provide insights into how bacterial communities respond to seasonal environmental changes, uncovering underlying mechanisms governing community assembly in subtropical rivers, which are crucial for the effective management and conservation of riverine ecosystems.